Impact of Saccharomyces cerevisiae and Lactobacillus buchneri on microbial communities during ensiling and aerobic spoilage of corn silage() - Xu, Shanwei (J Anim Sci, 2019)
The objective of this study was to assess the impact of Saccharomyces cerevisiae in combination with Lactobacillus buchneri on the fermentation characteristics, aerobic stability, nutritive value, and microbial communities of corn silage. Whole crop corn (39% DM) was either uninoculated (Control) or inoculated with S. cerevisiae and L. buchneri at the following concentrations: S. cerevisiae 10(4) cfu/g fresh forage (S4), S. cerevisiae 10(5) cfu/g (S5), S. cerevisiae 10(4) cfu/g + L. buchneri 10(5) cfu/g (S4L5), and S. cerevisiae 10(5) cfu/g + L. buchneri 10(4) cfu/g (S5L4), and ensiled in mini silos for 118 d, followed by 7 d of aerobic exposure. Changes in fermentation characteristics and nutritive value were assessed in terminal silages. Saccharomyces cerevisiae, L. buchneri, and total yeast, fungal, and bacterial communities in silage were estimated using quantitative PCR. Composition of bacterial and fungal communities during ensiling and aerobic exposure was measured using 16S rDNA and ITS sequencing, respectively. In the first 7 d of ensiling, the concentration of lactic acid rapidly increased (P < 0.01) in all silages, with the pH declining to 4.0 (P < 0.001) and thereafter remaining stable (P = 0.23). Although S4L5 contained a higher (P = 0.03) concentration of acetic acid than Control, other fermentation characteristics were did not differ among terminal silages. Inoculation with S. cerevisiae had no detrimental effect on the aerobic stability of silage, whereas L. buchneri did not prevent spoilage as the pH across all silages averaged 8.0 after 7 d of aerobic exposure. Total yeast (P = 0.42), bacterial (P = 0.13), and fungal (P = 0.89) communities were not altered by the inoculants after ensiling or aerobic exposure. Sequencing identified temporal shifts of bacterial and fungal communities during ensiling and aerobic exposure. Concentrations of S. cerevisiae and L. buchneri in all inoculated silages remained greater (P < 0.01) than Control after ensiling, with numbers of S. cerevisiae increasing after 7 d of aerobic exposure. Bacterial communities in silages inoculated with S. cerevisiae and L. buchneri clustered separately from other silages, an observation that was not apparent for fungal communities. Our findings suggest that aerobic exposure could potentially increase the abundance of S. cerevisiae with probiotic properties in corn silage just prior to feeding.